Penerapan Model Guided Discovery Learning Berbasis LKPD Untuk Meningkatkan Hasil Belajar Matematika - Purwanti Purwanti (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
This Research is based on teaching and learning process in SMP Negeri 2 Malinau Selatan Hilir. The purpose of the research was to improve student achievement in learning after implementation of Guided Discovery Learning. The target of this research were the 7th grade students which amounts to 7 students. This type of research is a Classroom Action Research with three cycles. The initial condition based on dayli test values KD 3.4 showed that the score was 58,57 with the total number of students who passed were only 3 students and the number of students who hasn’t passed were 4 students. At the first cycle of mathematics learning the outcomes increased to become 64,57. At the second cycle the outcomes increased to become 72,57 and in the third cycle of mathematics learning the outcomes increased to become 75,00. The percentage of student learning completeness also increased. At the first cycle completeness only 57,14%, the second cycle increase become 85,71% and the thiird cycle of students completeness reach 100%, thus it can be concluded that the Guided Discovery Learning based LKPD model can improve student learning outcomes.